Titanium aminophosphates: synthesis, characterization and crystal violet dye degradation studies. Issue 1 (21st December 2015) - Anumula, Rajini; Adepu, Ajay Kumar; Chirra, Suman; Siliveri, Suresh; Narayanan, Venkatathri
Abstract : Titanium aminophosphates are prepared using titanium tetraisopropoxide, orthophosphoric acid and aliphatic amines. Their detailed characterization and catalytic crystal violet dye degradation were studied. Abstract : Titanium aminophosphates are prepared by using titanium tetraisopropoxide, orthophosphoric acid and aliphatic amines. The synthesized titanium n -propylaminophosphate (TNPAP), titanium n -octylaminophosphate (TNOAP) and titanium n -dodecylaminophosphate (TNDDAP) are characterized by various physicochemical techniques. The powder X-ray diffraction pattern of titanium aminophosphates suggests the presence of a –Ti–O– phase. The percentage of titanium incorporated (P/Ti = 100) into the frameworks of the titanium aminophosphates have been confirmed from EDAX analysis. The infrared and Raman spectra infer the presence of peaks due to the vibrational bands of Ti–O, P–O and Ti–O–P linkages. The Ultraviolet-Visible diffuse reflectance spectra reveal the presence of tetrahedral co-ordination of Ti in the framework. The X-ray photoelectron spectra suggest the presence of an –O–Ti–N– or –Ti–N–O– framework in TNPAP. The 31 P MASNMR spectra of titanium aminophosphates indicate the presence of tetrahedrally co-ordinated phosphorous in the framework. The catalytic effect of TNPAP, TNOAP and TNDDAP has been studied for the degradation of crystal violet dye. TNPAP has been found to be more efficient for the degradation of crystal violet, indicating the specificity of this catalyst. The optimum conditions required for the efficient degradation of crystal violet dye have been established as pH = 5.1, [H2 O2 ] = 1.0 × 10 −3 M, [CV] = 8.0 × 10 −4 M and TNPAP catalyst dosage of 150 mg. About 91% of the crystal violet dye has been degraded by TNPAP in 165 min. These catalysts exhibited good reusability over five successive cycles. They have the potential to be used as economical catalysts for dye degradation of industrial waste waters.